2017
DOI: 10.1002/cncr.31086
|View full text |Cite
|
Sign up to set email alerts
|

Association between serious psychological distress and nonparticipation in cancer screening and the modifying effect of socioeconomic status: Analysis of anonymized data from a national cross‐sectional survey in Japan

Abstract: BACKGROUND It is unclear whether individuals who have serious psychological distress (SPD) are less likely to participate in screening tests for gastric cancer, lung cancer, and other types of cancer. Of the few studies that have examined the association between SPD and participation in cancer screening, none have reported modifying effects of educational, marital, or employment status. METHODS The authors analyzed a national representative data set from the 2010 Comprehensive Survey of Living Conditions of Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
3
10
1
Order By: Relevance
“…People with mental disorders often experience problems such as lack of exercise, 26,27 poor eating habits, 26,28 obesity, 28,29 high rates of smoking or substance abuse, 26,[30][31][32][33][34] and low cancer-screening rates. [9][10][11][12] Consistent with previous papers, [19][20][21][22][23] the present study showed that these patients need support in the prevention and early detection of cancer.…”
Section: Patient Levelsupporting
confidence: 91%
“…People with mental disorders often experience problems such as lack of exercise, 26,27 poor eating habits, 26,28 obesity, 28,29 high rates of smoking or substance abuse, 26,[30][31][32][33][34] and low cancer-screening rates. [9][10][11][12] Consistent with previous papers, [19][20][21][22][23] the present study showed that these patients need support in the prevention and early detection of cancer.…”
Section: Patient Levelsupporting
confidence: 91%
“…found a positive correlation between the perceived risk and a family history of cancer in men screened for prostate carcinoma and that these men had a particularly high level of psychological distress 17. In a study by Fujiwara et al ., the level of education of participants with serious psychological distress significantly increased their willingness to participate in cancer screening 16. However, in the current study, education level of the participants had no significant effect on the PCQ results.…”
Section: Discussioncontrasting
confidence: 72%
“…This finding might be due to the fact that younger women are more aware of disease consequences and treatments available 15. Several other studies have also shown an inverse relationship between age and psychological outcomes 16…”
Section: Discussionmentioning
confidence: 93%
“…Higher education tends to be associated with less manual labor (fewer physical activities), stressful work, late age at first birth, and null parity, factors known to increase the incidence of breast cancer, whereas cervical cancer is largely caused by infection with human papillary virus, which might explain the difference between the impact of education on the incidence rates of these two cancers . Interestingly, while education level could modify the effect of psychological distress on accepting screening for colorectal and lung cancers, it did not exhibit this effect on breast cancer screening in countries with low cancer screening rates . From the perspective of survival, our study supported education as a protective factor for BCSS and OS (Table ), which was consistent with results of previous studies in which women with high education levels had better survival than women with low education levels, which suggests that education helps women understand the benefits of conducting breast self‐examination and accepting routine breast cancer screening programs, and it can improve patient access to effective treatments .…”
Section: Discussionmentioning
confidence: 56%